The Battle of Trafalgar and its impact on the economic policies of France and Great Britain during the Napoleonic wars - Gärtner,Carl Fredrik (2023)
The Napoleonic wars have been extensively analyzed, revealing their significant economic aspects. This thesis adopts an economic history perspective to explore the Battle of Trafalgar’s impact on the economic policies of France and Great Britain. Through a literature analysis and theoretical framework of economic warfare, war finance and Mercantilist theory, this thesis sheds light on the battle’s effects on trade, naval power and colonial endeavors. While the battle resulted in the Royal Navy’s dominant naval position, its broader economic impact remains subject to interpretation.
Keywords: Economic history; Economic warfare; War finance; Mercantilism; Napoleonic wars; Battle of Trafalgar